Salvia uliginosa Bog Sage, Bog Salvia: FPS529/FP529, 8/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of Salvia uliginosa, commonly known as Bog Sage or Bog Salvia. It describes the plant as an upright to spreading perennial that can reach heights of 3 to 4 feet. The plant is versatile, serving as a ground cover or background plant, and is particularly attractive when paired with ornamental grasses. It thrives in full sun to partial shade and can adapt to both wet and dry conditions, although it can become invasive in wet areas. The document also provides guidance on propagation methods and notes that Bog Sage has no major pest or disease concerns. Original publication date October 1999.